Gynecological Disease Diagnosis Expert System Using the Web-Based Dempster Shafer Method - Lola Herawati; Ade Eviyanti (Universitas Muhammadiyah Sidoarjo, 2021)
Uterine disease is a disease that generally attacks female reproduction. Most women know a disease that is in their womb when the disease is declared severe or so-called advanced stage. With this expert system, it is hoped that human uterine diseases can be detected early and can minimize the occurrence of more dangerous diseases. The method used in this expert system is the Dempster Shafer calculation method. This expert system works by entering the symptoms experienced by the patient after which the system will work according to the calculations determined by the expert who entered the knowledge base. The result of this research is to build an expert system for diagnosis of gynecology using a website-based dempster shafer. This website can be used as the use of technology so that it can be used to diagnose uterine diseases precisely and accurately, so that people with gynecological diseases are handled more quickly from an early age.